Pairing of white wine made with shade-grown grapes and Japanese cuisine - Takuji Takahashi (Nature Portfolio, 2021)
Abstract This study investigated the effect of pairing of wine vinified from shade-grown grapes before onset of ripening on the palatability of sashimi, a typical Japanese cuisine. GC-MS analyses of volatile chemicals revealed that shading reduced phenolic compounds and terpenoids, and added fatty acid ethyl esters which are also known to contribute to the flavor of Japanese sake. When the pairing of sashimi with wine was evaluated by individuals who regularly drink Japanese sake during meals, shade wine was more highly rated than wine made from normally-grown grapes.